The potency of propolis extract as anti-inflammatory agent for stimulation of reparative dentin formation - Anindya, Cinitra; Widjiastuti, Ira; Zubaidah, Nanik (Conservative Dentistry Journal, 2023)
Background: As an effort to treat a deep caries lesion with a diagnosis of reversible pulpitis, one of the treatment options is pulp capping. For decades, calcium hydroxide has been considered the most acceptable pulp capping material and has been routinely used in dental practice, but it also has some weakness. To overcome that, alternative materials are needed that can provide a better effect. Recently, a lot of research has been done using natural ingredients, including Propolis. Propolis has been known to have strong antimicrobial and anti inflammatory properties. Therefore, it is necessary to conduct a deeper study regarding the potency of propolis extract as an anti inflammatory agent for the stimulation of reparative dentin formation so that it can be considered to be used as a pulp capping material. Objective: The aim of this literature review is to highlight the potency of propolis extract as anti inflammatory agent in the natural stimulation of reparative dentin formation. Methods: The search strategy consist of an electronic research using databases such as PubMed, Google Scholar, Science Direct, dan Springer Link for studies published from 2003 to 2021 regarding the potency of propolis extract as anti inflammatory agent for stimulation of reparative dentin formation, including review articles and research articles. Results: Propolis and its constituents have been proven to be used as a potent natural anti inflammatory, it also considered to have the ability to promote reparative dentin formation. However, there are some literatures stated that reparative dentin does not form with the application of propolis, and the causes may vary. Conclusion: Propolis extract has a potency as an anti inflammatory agent in dental pulp inflammation by inhibiting TNFα expression, and increasing TGF-β1 expression, as well as its potency in stimulating the formation of reparative dentin. Based on this review, further studies are needed.